Subpatent infection with nucleoside transporter 1-deficient Plasmodium blood stage parasites confers sterile protection against lethal malaria in mice - ALY, AHMED SAYED IBRAHıM; Aly, Ahmed Sayed Ibrahım; Downie, Megan J.; Ben Mamoun, Choukri; Kappe, Stefan H. I. (My University, 2010)
P>Repeated immunizations with whole Plasmodium blood stage parasites and concomitant drug cure of infection confer protective immunity against parasite challenge in mice, monkeys and humans. Moreover, it was recently shown that infections with genetically modified rodent malaria blood stage parasites conferred sterile protection against lethal blood stage challenge. However, in these models vaccination resulted in high parasitemias and, in consequence, carries risk of vaccine-induced pathology and death. Herein, we generated a novel, completely blood stage-attenuated P. yoelii rodent malaria strain by targeted deletion of parasite nucleoside transporter 1 (NT1). Immunization of inbred and outbred mouse strains with a single low dose of Pynt1- blood stages did not induce any patent infections and conferred complete sterile protection against lethal heterologous blood stage and sporozoite challenges. Partial protection was observed against lethal challenges with another parasite species, P. berghei. Importantly, subcutaneous immunization with Pynt1- conferred sterile protection against lethal blood stage challenges. We show that cellular and humoral immune responses are both essential for sterile protection. The study demonstrates that genetic manipulation provides a platform for the designed, complete attenuation of malaria parasite blood stages and suggests testing the safety and efficacy of P. falciparum NT1 knockout strains in humans.